Nutrient Dynamics Modulated by Diapycnal Mixing and Particle Sinking Pathways Within an Intrathermocline Eddy in the Tropical Western North Pacific - Zhendong Hu; Zhiyu Liu; Xin Liu; Takako Masuda; Takuhei Shiozaki; Hiroyuki Yamada; Hongyang Lin; Bangqin Huang; Ken Furuya (Geophysical Research Letters, 2025)
Abstract Oceanic subsurface eddies are believed to potentially impact biogeochemical cycles; however, our understanding remains limited due to sparse in situ observations. This study presents observation of an intrathermocline eddy (ITE) in the tropical western North Pacific and provides a comprehensive analysis of how ITE modulate nutrient dynamics by both diapycnal mixing and lateral transport. Pronounced upward nutrient fluxes were observed within the deep chlorophyll maximum layer due to ITE‐induced mixing. Lateral transport directly influenced nutrient concentrations through isopycnal advection and indirectly by regulating the horizontal distribution of sinking particles. The latter likely induced spatial variability in mineralization, which played a dominant role in shaping nutrient enrichment. This study advances our understanding of the biogeochemical impacts of ITE, presenting a new paradigm for their role in nutrient and carbon cycling in oligotrophic oceans.